The History of the Priority Di∫pute between Newton and Leibniz Mathematics in History and Culture - Sonar, Thomas (Springer International Publishing, 2018)
This book provides a thrilling history of the famous priority dispute between Gottfried Wilhelm Leibniz and Isaac Newton, presenting the episode for the first time in the context of cultural history. It introduces readers to the background of the dispute, details its escalation, and discusses the aftermath of the big divide, which extended well into recent times. One of the unique features of the book is that the mathematics behind the story is very intelligibly explained - an approach that offers general readers interested in the history of sciences and mathematics a window into the world of these two giants in their field. From the epilogue to the German edition by Eberhard Knobloch: Thomas Sonar has traced the emergence and the escalation of this conflict, which was heightened by Leibniz's rejection of Newton's gravitation theory, in a grandiose, excitingly written monograph. With absolute competence, he also explains the mathematical context so that non-mathematicians will also profit from the book. Quod erat demonstrandum! From the reviews for the German language edition ..... This book provides a vivid and easy-reading picture of many political and scientific aspects of the end of the 17th and the beginning of the 18th century, and constitutes an excellent guide to the existing secondary literature for laymen as well as for specialists.... Stefan Neuwirth in: Zentralblatt MATH 1343 - 1 (1343.01005) An extremely readable book on one of the most memorable episodes in the history of sciences. Manfred Jacobi in: Physik in unserer Zeit, Jg. 47, Heft 5, September 2016.